Catalytic Profile Reactor for Multimodal Operando Measurements during Periodic Operation. Issue 24 (22nd November 2022) - Espinoza, Diego; Wollak, Birte; Sheppard, Thomas L.; Dippel, Ann‐Christin; Sturm, Marina; Gutowski, Olof; Schmidt, Michael; Korup, Oliver; Horn, Raimund
Abstract: Multimodal operando measurement concepts aim to provide structure‐activity relations of heterogeneously catalyzed reactions during operation. While the utilization of multiple characterization and spatiotemporally‐resolved techniques provides complementary information at relevant time and length scales, different reactor operation modes allow to track catalyst dynamics. However, combining these measurement concepts require complex experimental setups with high demands from a strongly interdisciplinary field of reaction engineering, physics and chemistry. In this study, a fully automated and integrated catalytic profile reactor setup is introduced which is capable of measuring spatiotemporally‐resolved species concentration, temperature and catalyst structure information under periodic reaction conditions. The oxidative dehydrogenation of C2 H6 to C2 H4 over MoO3 /γ‐Al2 O3 was used as a test system. Using the periodic profile approach, the catalytic system was investigated through activity measurements resolved in time and space combined with reactor simulations and operando high‐energy X‐ray diffraction. The presented catalytic profile reactor setup is a versatile technology, aiming to promote combined and detailed analysis of local catalyst activity and structure, for improved reproducibility and quality of operando measurements. Abstract : Multimodal operando measurement concepts in heterogeneous catalysis are essential in providing a holistic picture of the catalyst at work. This study introduces a flexible catalytic profile reactor setup capable of measuring spatiotemporally‐resolved temperature, gas and spectroscopic or diffraction profiles during periodic reactor operation, applicable at synchrotron and laboratory facilities.